Effect of Intensive Blood Pressure Control on Cardiovascular Remodeling in Hypertensive Patients with Nephrosclerosis - Otelio Randall; John Kwagyan; Tamrat Retta; Kenneth Jamerson; Velvie Pogue; Keith Norris; Muluemebet Ketete; Shichen Xu; Tom Greene; Xuelei Wang; Lawrence Agodoa (International Journal of Nephrology)
Pulse pressure (PP), a marker of arterial system properties, has been linked to cardiovascular (CV) complications. We examined (a) association between unit changes of PP and (i) composite CV outcomes and (ii) development of left-ventricular hypertrophy (LVH) and (b) effect of mean arterial pressure (MAP) control on rate of change in PP. We studied 1094 nondiabetics with nephrosclerosis in the African American Study of Kidney Disease and Hypertension. Subjects were randomly assigned to usual MAP goal (102–107 mmHg) or a lower MAP goal (≤92 mmHg) and randomized to beta-blocker, angiotensin converting enzyme inhibitor, or calcium channel blocker. After covariate adjustment, a higher PP was associated with increased risk of CV outcome (RR = 1.28, CI = 1.11–1.47, P<0.01) and new LVH (RR = 1.26, CI = 1.04–1.54, P=0.02). PP increased at a greater rate in the usual than in lower MAP groups (slope ± SE: 1.08 ± 0.15 versus 0.42 ± 0.15 mmHg/year, P=0.002), but not by the antihypertensive treatment assignment. Observations indicate that control to a lower MAP slows the progression of PP, a correlate of cardiovascular remodeling and complications, and may be beneficial to CV health.